The study of changes in tear film and tear film secretion before and after refractive surgery - Hassan S. Yousef; Abdel H.E. Elaskary; Aya M. Hosny (Al-Azhar Assiut Medical Journal)
Background and aim Dry eye can be initiated or exacerbated by refractive surgery. Dry eye syndrome causes discomfort, variations in visual quality, epithelial damage, and slower healing and can lead to refractive error regression and decreased visual acuity. The study aims to compare tear film and tear secretion before and after refractive surgery. Patients and methods Fifty patients (18–41 years old) (24 males and 26 females) were examined by Mediworks Dry Eye Diagnostic System and Schirmer I test prerefractive and postrefractive surgery and followed up 2 weeks, 1, 3, and 6 months postoperative. Results Preoperative and postoperative 2 weeks, 1, 3, and 6 months tear break-up time differences showed highly statistically significance with P value of 0.001, 0.001, 0.001, and 0.001, respectively. Preoperative and postoperative 2 weeks, 1, and 3 months follow-up of Schirmer I test were statistically highly significant with P value of 0.001, 0.001, and 0.001, respectively. However preoperative, and postoperative 6 months showed insignificant difference with P value of 0.531. Preoperative and postoperative 2 weeks, 1, 3, and 6 months follow-up of uncorrected visual acuity, were all statistically significant with P values of 0.001, 0.001, 0.001, and 0.001, respectively. Conclusion Postrefractive surgery patients had worse ocular surface status than normal controls. Reduced tear break-up time and Schirmer I test results, and decreased functional visual acuity, are clinical indicators of postrefractive surgery dry eye. A few patients continue to have symptoms more than 6 months after surgery.